The nuclear receptor constitutive androstane receptor/NR1I3 enhances the profibrotic effects of transforming growth factor β and contributes to the development of experimental dermal fibrosis - Avouac, Jerome; Palumbo-Zerr, Katrin; Ruzehaji, Nadira; Tomcik, Michal; Zerr, Pawel; Dees, Clara; Distler, Alfiya; Beyer, Christian; Schneider, Holm; Distler, Oliver; Schett, Georg; Allanore, Yannick; et al. (Arthritis and Rheumatology, 2014)
Objective Nuclear receptors regulate cell growth, differentiation, and homeostasis. Selective nuclear receptors promote fibroblast activation, which leads to tissue fibrosis, the hallmark of systemic sclerosis (SSc). This study was undertaken to investigate the effects of constitutive androstane receptor (CAR)/NR1I3, an orphan nuclear receptor, on fibroblast activation and experimental dermal fibrosis. Methods CAR expression was quantified by quantitative polymerase chain reaction, Western blotting, immunohistochemistry, and immunofluorescence. CAR expression was modulated by small molecules, small interfering RNA, forced overexpression, and site-directed mutagenesis. The effects of CAR activation were analyzed in cultured fibroblasts, in bleomycin-induced dermal fibrosis, and in mice overexpressing a constitutively active transforming growth factor β (TGFβ) receptor type I (TβRI-CA). Results Up-regulation of CAR was detected in the skin and in dermal fibroblasts in SSc patients. Stimulation of healthy fibroblasts with TGFβ induced the expression of CAR messenger RNA and protein in a Smad-dependent manner. Pharmacologic activation or overexpression of CAR in healthy fibroblasts significantly increased the stimulatory effects of TGFβ on collagen synthesis and myofibroblast differentiation, and amplified the stimulatory effects of TGFβ on COL1A2 transcription activity. Treatment with CAR agonist increased the activation of canonical TGFβ signaling in murine models of SSc and exacerbated bleomycin-induced and TβRI-CA-induced fibrosis with increased dermal thickening, myofibroblast counts, and collagen accumulation. Conclusion Our findings indicate that CAR is up-regulated in SSc and regulates TGFβ signaling. Activation of CAR increases the profibrotic effects of TGFβ in cultured fibroblasts and in different preclinical models of SSc. Thus, inactivation of CAR might be a novel approach to target aberrant TGFβ signaling in SSc and in other fibrotic diseases.
CRIS-Team Scopus Importer:2020-07-01